Peran Suami terhadap Istri yang Menderita Kista Ovarium di Purwokerto - Triyanto, Endang; Handoyo, (Jurusan Keperawatan FIKES UNSOED, 2009)
Disorders of the women ovary can lead to impaired growth and development as well as maturity of the ovum, so that it could make high risk for women to become fertile. The most disorder that commonly occurred in women is ovarian cysts. This situation become worst if her husband doesn’t support and tend to blame his wife. The purpose of this study is to determine the role of husband to his wife who suffered from ovarian cysts. This research is descriptive study with a survey approach. Sampling techniques performed in this study is total sampling. Respondents were ovarian cyst women who had a treatment at Margono Soekardjo Hospital of Purwokerto during April to June 2009. The results of this study show that 17 (25%) respondents fully support and 33(49%) fairly support his wife. Meanwhile, 15(22%) and 3 (4%) respondents have less and no support by her husband during get some treatments. From three type of husband role support, instrumental support has the highest score at (41%). In addition, emotional and informational support have score at (33%) and (26%) respectively.